Mengungkap Peran Good Corporate Governance dan Leverage dalam Mendorong Pengungkapan CSR: Studi pada Perusahaan Energi Di BEI - Findayani, Vinka; Tutuko, Bambang; Saraswati, Ade Maya (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2025)
This study examines how independent boards of commissioners, audit committee size, board of directors size, debt to equity ratio, and debt to asset ratio influence CSR disclosure. The sample consists of 12 companies in the energy sector, covering the coal and oil and gas subsector, listed on the Indonesia Stock Exchange (IDX) during the period 2020-2023. Sample selection was applied through purposive sampling using secondary data. The regression result show that independent boards of commissioners have a negative effect. Audit committee size and board of directors size have a positive effect. The debt to equity ratio has a negative effect, while the debt to asset ratio does not show any effect. Simultaneously, all independent variables have a significant effect on CSR disclosure, with an adjusted R2 value of 0.338. The contribution of this study can advance knowledge and serve as a reference for practitioners in conducting research.